Maternally Inherited Type 2 Diabetes and Deafness: Clinical and Molecular Aspect in Pakistan - Maryam Wahid, Abdul Khaliq Naveed (Journal of Rawalpindi Medical College, 2009)
Background:. A3243G mutation in tRNA Leu (UUR) leads to a specific clinical syndrome characterized by diabetes and sensorineural hearing defect, hence called as “Maternally Inherited Diabetes and Deafness (MIDD)”.. Methods: The study was retrospective, analytical case control study. Non - probability convenient sampling technique was used. Subjects were divided into two groups. Thirty-nine patients with phenotype of mitochondrial diabetes and a strong maternal history of diabetes (group 1) and 40 non – diabetic individuals (controls) with no maternal history of diabetes (group 2). MtDNA, isolated from peripheral blood leukocytes, was analyzed to detect A3243G tRNALeu(UUR) gene mutation .Results: In spite of the presence of characteristic features of maternally inherited diabetes and deafness, A3243G tRNALeu(UUR) gene mutation was absent in patients and controls. Mean age of onset of diabetes was +34.06 years and of deafness was +47.56 years. Mean plasma glucose, HbA1c, cholesterol and triglyceride level in patients was significantly higher (p< 0.001) whereas body mass index (BMI) of diabetics was significantly low (p< 0.001) as compared with controls. Conclusion: Although A3243G tRNALeu(UUR) gene mutation was not likely to be a frequent cause of mitochondrial diabetes in selected group of patients, other mitochondrial diabetogenic mutations as well as mechanisms involved in pathogenesis of mitochondrial diabetes must be considered.